2016
DOI: 10.1038/srep23838
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Additional Intra-aortic Balloon Counter-Pulsation Therapy to Cardiogenic Shock Patients Supported by Extra-corporeal Membranous Oxygenation

Abstract: Extra-corporeal membranous oxygenation (ECMO) has been applied in patients with cardiopulmonary failure. One critical drawback of peripheral ECMO is an increase in left ventricular (LV) afterload which could be counterbalanced by the combination of intra-aortic balloon counter-pulsation (IABP) therapy. We hypothesized that an add-on therapy with IABP could improve outcomes in patients receiving ECMO support. We included patients (>18 years old) from 2002 to 2013 requiring ECMO support due to cardiogenic shock … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 31 publications
4
39
0
5
Order By: Relevance
“…Again, the same conclusions were reported by Lin et al in 529 patients (227 used ECMO alone and 302 combined IABP plus V‐A ECMO) …”
Section: Percutaneous Venting Of the Left Ventriclesupporting
confidence: 78%
“…Again, the same conclusions were reported by Lin et al in 529 patients (227 used ECMO alone and 302 combined IABP plus V‐A ECMO) …”
Section: Percutaneous Venting Of the Left Ventriclesupporting
confidence: 78%
“…Similarly, Aso et al reported that 28‐day mortality and in‐hospital mortality were significantly lower in the combined group . However, Lin et al found the mortality rates at two weeks after ECMO implantation were not different between the ECMO group and combined group , which was consistent with a systematic review stating that there was a lack of survival benefit when using combined IABP and ECMO . Previous study included patients with all indications for short‐term mechanical circulatory support, which would induce confounding factors when interpreting the yield of combined use.…”
Section: Discussionsupporting
confidence: 55%
“…The remaining 29 publications were reviewed in full-text and assessed against inclusion criteria. Finally, 12 studies were included in our study (5,(7)(8)(9)(15)(16)(17)(18)(19)(20)(21)(22). The search and selection process is depicted in a PRISMA flow diagram ( Figure 1).…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…However, the results from SHOCK II trial suggested that IABP did not reduce 30‐days mortality in patients with cardiogenic shock . The outcomes of IABP combined with VA‐ECMO were also disappointing in some observational studies , but a relatively small number of patients were enrolled.…”
Section: Discussionmentioning
confidence: 99%